No affair before us of greater concern : the war at sea in Ireland, 1641-1649 - Murphy, Elaine (Trinity College (Dublin, Ireland). Department of History, 2007)
This thesis examines the war at sea in Ireland between 1641 and 1649. The significance of the maritime conflict that took place on the Irish coast has been overshadowed by the military campaigns on land during this decade. This study therefore aims to put forward a reassessment of the importance of naval warfare in the waters around Ireland to the war in the three kingdoms in the 1640s. This dissertation takes a chronological and analytical approach to the war at sea in order to quantify and evaluate the efforts of the three opposing naval forces in Ireland. Chapter 1 considers the importance of harbours and coastal fortifications along the Irish seaboards to the various fleets.
Keywords: Modern History, Ph.D.; Ph.D. Trinity College Dublin